The Impact of Oil Prices on the Global Competitiveness of National Economies - Mukhamediyev, Bulat; Temerbulatova, Zhansaya (International Journal of Energy Economics and Policy, 2019)
The influence of various factors on the competitiveness of national economies is investigated in many articles, however, there is little research on the impact of resource prices on it. This article aims to examine the effect of crude oil prices on the global competitiveness of both producing countries and countries consuming oil. Based on annual data from 60 countries for 2006–2017, a regression analysis of panel data with fixed effects shows that exceeding the annual growth rate of oil prices over GDP growth rates reduces the growth rate of the global competitiveness index, and it is twice strong for oil exporting countries than for countries non-oil exporters. And the growth of average labor productivity, total factor productivity, the share of employed in the total population, High-technology exports, and the Gross capital formation raises the country’s global competitiveness index. Due to the rise in world oil prices, exporting countries are moving downward in the global competitiveness ranking more than non-oil exporters. Keywords: oil price, global competitiveness index, panel data JEL Classifications: C33, C55, F6, O47 DOI: https://doi.org/10.32479/ijeep.8089